2017
DOI: 10.1111/vru.12529
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic morphometry of tympanic bulla shape and position in brachycephalic and mesaticephalic dog breeds

Abstract: Anatomic variations in skull morphology have been previously described for brachycephalic dogs; however there is little published information on interbreed variations in tympanic bulla morphology. This retrospective observational study aimed to (1) provide detailed descriptions of the computed tomographic (CT) morphology of tympanic bullae in a sample of dogs representing four brachycephalic breeds (Pugs, French Bulldogs, English Bulldog, and Cavalier King Charles Spaniels) versus two mesaticephalic breeds (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 19 publications
3
51
0
Order By: Relevance
“…It is known that narrow conformation of the ear canals may predispose to otitis, but an abnormal OTIS‐3 score was a surprisingly rare finding in the dogs in our study. Previous studies have demonstrated a higher prevalence of subclinical middle ear effusion in brachycephalic dogs of various breeds . However, only a small number of dogs in these studies were EBs.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…It is known that narrow conformation of the ear canals may predispose to otitis, but an abnormal OTIS‐3 score was a surprisingly rare finding in the dogs in our study. Previous studies have demonstrated a higher prevalence of subclinical middle ear effusion in brachycephalic dogs of various breeds . However, only a small number of dogs in these studies were EBs.…”
Section: Discussionmentioning
confidence: 90%
“…Brachycephalic dog breeds, such as the EB, have a congenitally flattened facial anatomy. This conformation is associated with several malformations of the head and neck and also has been shown to affect the structure of the ear . Brachycephalic dogs have been reported to possess a significantly thicker tympanic bulla wall and a lower tympanic bulla volume than nonbrachycephalic dogs .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations